SMAS: A solution-based multi-agent system for improving problem solving skills in computer programming - Hooshyar, Danial; Ahmad, Rodina; Md Nasir, Mohd Hairul Nizam (University of Kuwait, 2017)
In this research, a solution-based multi-agent system (SMAS) is proposed, which benefits from a novel automatic text-to-flowchart conversion approach in order to improve students' problem solving skills. The aim is to introduce the early stages of learning programming (CS1). By using SMAS, students can focus on solution designing activities in the form of flowchart development more than on language and syntax. Ultimately, an experimental study is devised to assess the success of SMAS as a tool to aid students with problem solving activities and learning computer programming. In total, 30.4% of problems that were left unresolved in previous sessions were solved by students in the control group, whereas 69.7% of previously unresolved problems were solved by students in the experimental group who used SMAS. Therefore, the use of SMAS in practice is supported, as the results indicate considerable gains for the experimental group over the control group.